PREDICTORS OF HIV STATUS DISCLOSURE AND CONDOM USE AMONG MOTHERS LIVING WITH HIV IN A TERTIARY HOSPITAL SOUTHEAST, NIGERIA. - ORJI , Maria-Lauretta Chito; OKICHE , Chikosolu Yvonne; AGBOEZE , Joseph; Ifeoma, Joe-Akunne Chinwe; OTUBO , Sunday Austin; NWALI , Matthew Igwe; ONYIRE , Nnamdi Benson (African Journal of Infectious Diseases (AJID), 2024)
Background: Non-disclosure of HIV status and poor condom use, among mothers living with HIV may pose risks of HIV transmission to their serodiscordant partners and may influence the outcome of their infants. The study was aimed at assessing predictors of HIV status disclosure, and condom use, among mothers of infants exposed to HIV attending the ART clinic in Abakaliki, Southeast Nigeria. Materials and Methods. A hospital-based cross-sectional study that involved 246 mothers living with HIV. Information was obtained using an interviewer-administered structured questionnaire. Data was analysed using SPSS version 26 and p<0.05 was considered statistically significant. Results: A total of 190 (77.2%)of the 246 study participants disclosed their HIV status to their partners, but only 95 (38.6%) of them used condoms consistently and correctly during sexual intercourse. While 112(45.5%) had HIV serodiscordant partners, 29 (11.8%) did not know the HIV status of their partners. Marital status of the mother (p=0.041), and HIV serostatus of the partner (p<0.001) having a child living with HIV (p=0.035) were predictors of HIV status disclosure to partners while HIV serostatus of the partner (p=0.041), the total number of children (p=0.031) and history of STDs (p=0.008) were predictors of condom use. Mothers with serodiscordant partners (AOR=2.21,95%CI=0.94-11.32) and mothers with less than 4 children (AOR=1.89, 95%CI= 0.52-8.33) were about twice more likely to use condoms compared to their colleagues. Conclusion: HIV serostatus of partners predicted status disclosure and condom use. Effective counseling is recommended to improve status disclosure and condom use especially among serodiscordant couples.